Compared biology of tetranychus urticae in cotton cultivars. II. Life table of fertility - Silva, Marineide de Andrade; Parra, José Roberto Postali; Chiavegato, Luiz Gonzaga (Pesquisa Agropecuaria Brasileira, 2014)
This paper is part of a research that aims to evaluate the Tetranychus urticae (Koch, 1836) (Acari: Tetranychidae) behavior in cotton cultivars IAC-17, IAC-18 and IAC-19. The biological cycle data has been already submitted in a previous work. In order to elaborate the life tables, two experiments were conducted, 1980/81 and 1981/82, with temperatures between 24,0 and 26,0 °C, air relative humidity between 52,0 and 62,0%, and photoperiod of 14 hours. Individualized mites were observed daily on leaf disks. Under these conditions, there was no statistical difference among the cultivars relative to the daily egg-laying capacity of T. urticae, but less mites have survived on ‘IAC-19’. Besides that, the mites occurring on this cultivar have presented the lowest net reproductive rate.